Synthesis of self-assembled polystyrene nanospheres/cadmium metal nanoparticles (PSNs/CdMNPs) composite thin film for its application as adsorbent and catalyst - Wibowa, Pratama Jujur (2015)
The research described in this dissertation is a comprehensive account of an attempt, for the first time, correlates the secondary pores structural and physicochemical properties of polystyrene nanospheres/cadmium metal nanoparticles (PSNs/CdMNPs) composite thin film with its adsorption and catalytic properties. The PSNs/CdMNPs composites were fabricated on a hydrophilic silicon wafer through self-assembly process from its aqueous colloidal. The existence of secondary pores and atomic particles of cadmium were clarified by using a field emission scanning electron microscopy (FESEM) and an energy dispersive X–ray (EDX) spectroscopy, respectively. Physical and chemical physical stability of the secondary pores were tested toward continuous laser irradiation of 633 nm wavelength and oxygen/argon reactive ion etching (O2/Ar RIE), respectively. Thermal catalytic effect of CdMNPs was investigated through thermogravimetry/differential thermal analysis (TG/DTA). Any chemical bond change of the PSNs/CdMNPs composite due to both CdMNPs and adsorbate molecules were confirmed by using an attenuated total reflectance–Fourier transform infrared (ATR–FTIR) spectroscopy. The capability of adsorption and catalysis of the secondary pores were clarified to adsorb and degrade tartazine as a model compound. It was found that the fabricated secondary pores were composed of dumbbell-like nanostructure with >100 nm pores in size had better adsorption capability than other adsorbents. It was demonstrated that the Freundlich constants ratio expressed as KF/n was 1.715 104. This value is much higher than previously reported for coconut shell activated carbon (CSAC), i.e. 0.158 and commercial activated carbon (CAC), i.e. 0.403. The rate of catalytic degradation of tartrazine on secondary pores was 0.718 μmol min–1 and a good agreement with pseudo first–order kinetics. Nanostructures of the secondary pores of PSNs/CdMNPs were not significantly changed under 633 nm continuous laser irradiation for 20 minutes as well as under O2/Argon RIE (30 sccm argon flow rate, 15 sccm oxygen flow rate, 20 seconds) suggesting a strong structural integrity of the secondary pores. Based on these results, it was concluded that PSNs/CdMNPs composites thin film secondary pores showed the adsorption and catalytic capabilities and is considered a potential adsorbent and catalyst.